Upaya Diplomasi Indonesia melalui Concrete Deliverables pada Presidensi G20 2022 - Haydar, Ahmad Faishal; Utomo, Ario Bimo (Prodi Ilmu Hubungan Internasional, Universitas Fajar, 2025)
Indonesia's G20 Presidency in 2022 marked a significant moment for the country to demonstrate global leadership amid geopolitical tensions and economic uncertainty. This study examines Indonesia's diplomatic efforts through concrete deliverables under the theme